Natural Resources of Rhaponticum carthamoides in the Tarbagatai State National Nature Park - Anar Myrzagaliyeva; Serik Irsaliyev; Shynar Tustubayeva; Talant Samarkhanov; Aidyn Orazov; Zhanylkan Alemseitova (Diversity)
The study of medicinal plants and having a protected status is an urgent issue for the conservation of biodiversity in Kazakhstan. Rhaponticum carthamoides (Willd.) Ilijn is a medicinal plant, and its excessive harvesting and destruction of habitats, as well as its conservation status, are of concern. We conducted a study to assess the ecological characteristics of the habitat of the species in the Tarbagatai National Natural Park, calculate the amount of medicinal raw materials, calculate both aboveground and underground phytomass, and calculate biological and operational reserves. A map has been developed to show the distribution of the species and potential harvest sites. In addition, a correlation analysis was performed to understand how population size affects productivity. The results highlight the need for continuous monitoring and protection of endangered species. The conservation of Rhaponticum carthamoides in the Tarbagatai State National Nature Park is currently ensured by its protected status. However, the study emphasizes the importance of developing a sustainable use regime to effectively manage plant resources and ensure their preservation for future generations.